(untitled) - Stewart, Mary (New York, 2012)
Launching the Imagination treats design as both a verb and a noun both a process and a product. Design is deliberate process of exploring multiple solutions and choosing the most promising option. Through an immersion in 2-D, 3-D, and 4-D concepts, students are encouraged to develop methods of thinking visually that will serve them throughout their studies and careers.
Keywords: Design,Thiết kế